Mallard Hybridization With Domesticated Lineages Alters Spring Migration Behavior and Timing - Nicholas W. Bakner; Nicholas M. Masto; Philip Lavretsky; Cory J. Highway; Allison C. Keever; Abigail G. Blake‐Bradshaw; Ryan J. Askren; Heath M. Hagy; Jamie C. Feddersen; Douglas C. Osborne; Bradley S. Cohen (Ecology and Evolution)
ABSTRACT Introgressive hybridization, the interbreeding and gene flow between different species, has become increasingly common in the Anthropocene, where human‐induced ecological changes and the introduction of captively reared individuals are increasing secondary contact among closely related species, leading to gene flow between wild and domesticated lineages. As a result, domesticated‐wild hybridization may potentially affect individual fitness, leading to maladaptive effects such as shifts in behavior or life‐history decisions (e.g., migration patterns), which could influence population demographics. In North America, the release of captive‐reared game‐farm mallards (Anas platyrhynchos) for hunting has led to extensive hybridization with wild mallards, altering the genetic structure in the Atlantic and Mississippi flyways. We aimed to investigate differences in spring migratory behavior among 296 GPS‐tagged mallards captured during winter in Tennessee and Arkansas with varying levels of hybridization. Despite relatively low levels of genetic introgression of game‐farm genes, mallards with higher percentages of game‐farm ancestry exhibited later departure and arrival times, shorter migration distances, and a tendency to establish residency at lower latitudes. Specifically, for every 10% increase in game‐farm genetics, mallards departed 17.7% later, arrived 22.1% later, settled 3.3% farther south, and traveled 7.1% shorter distances during migration. These findings suggest that genetic introgression from game‐farm mallards influences migratory behavior, potentially reducing fitness, and contributing to population declines in wild mallards. Our study presents a need for understanding how domestic hybridization effects fitness and behavioral change of other species.